Promotive Movement ’Kita Cinta’ as a Form of Community Empowerment in Efforts to Manage Stunting in Kampung Baru Tanjunganom Nganjuk Village - Aisyah, Siti; Suryani, Pudji; Rahayu, Dwi Estuning (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
The purpose of this Community Partnership Program is to socialize the understanding of mothers of toddlers and cadres about stunting management, one of which is the We Love Movement, Forming a community / network of mothers of toddlers about stunting management with the We Love Movement, Evaluating the understanding of toddler mothers about stunting management before and after socializing the We Love Movement. The method used consists of delivering material, questions and answers, games with leaflet media. The duration of the overall activity of this activity will be carried out for 2 months. The participants of mothers under five in Kampungbaru Village were 35 people and 5 cadres. Evaluation is carried out with pre test and post for knowledge and evaluation of our love ferakan which is carried out before and at the end of the activity. Based on the results of the activities that have been carried out in the form of socialization activities of the Kita Cinta Movement for mothers of toddlers totaling 35 people located in Kampungbaru Village, Tanjunganom District, Nganjuk Regency, it was found that before the activity was given, all mothers of toddlers stated that they had never known the activities of the Kita Cinta Movement, Overall the results of the assessment obtained before the activity were: Some of the items asked were several items that received low scores when measuring the understanding of toddler mothers with the following results: no toddler mothers had good understanding, 17Percent of mothers had poor understanding and 83Percent were sufficient. This result increased quite significantly after the socialization activity was carried out, namely with the following results: 68.5Percent good, 25.8 sufficient and 5.7Percent less. The conclusion of the community service activity of the community partnership program for the group of mothers under five is the socialization of the Kita Cinta Movement about parenting children to manage stunting in Kampungbaru Village, Tanjunganom Nganjuk District